Reduction of CXCR3 + CCR6 + CD4 + T Cells and IL ‐17+ RORγt + CD4 + T Cells During Secukinumab Treatment Identifies Patients With Axial Spondyloarthritis Responsive to Subsequent Biologic Therapy - Addison Pacheco; Patricia Remalante‐Rayco; Nigil Haroon; Denis Poddubnyy; Robert D. Inman (ACR Open Rheumatology, 2026)
Objective We recently reported an immune profile that stratifies patients with axial spondyloarthritis based on clinical response to secukinumab. We now undertake an exploratory study on the secukinumab nonresponder patients to determine if immunologic changes occur during their initial secukinumab treatment that could determine their next biologic response. Methods At the clinician's discretion, 18 patients who did not respond to secukinumab were either switched to a tumor necrosis factor inhibitor (TNFi; n = 8) or underwent secukinumab dose escalation to 300 mg monthly or 150 mg biweekly (n = 10). Flow cytometry–derived immune cell subset frequencies and NanoString gene expression profiling of CD45RO+CD45RA‐CD4+ T cells obtained during initial secukinumab treatment were stratified and reanalyzed according to subsequent treatment response based on the Bath Ankylosing Spondylitis Disease Activity Index at week 24. Results Most patients were either subsequent secukinumab responders (sSecu‐Rs; n = 5/10, 50%) or subsequent TNFi responders (sTNFi‐Rs; n = 6/8, 75%). During the initial secukinumab treatment, there was a significant decrease in the frequency of TH17.1 cells ( P < 0.05) and interleukin‐17 positive (IL17+) RORγt+ CD4+ T cells ( P < 0.05) in sSecu‐Rs and sTNFi‐Rs, but not in patients who failed all three biologics (subsequent non responder [sNR]). Multidimensional scaling of NanoString data revealed that subsequent nonresponders (sNRs; before and after secukinumab) clustered distinctly from other groups. Following the initial secukinumab therapy, but not before it, sSecu‐Rs and sTNFi‐Rs showed lower expression of IL12A , IL12RB1 , IFNGR1 , and JAK1 compared with sNRs. Conclusion Secukinumab treatment induces immunologic changes associated with reduced inflammation, even in patients who demonstrate an inadequate clinical response. Notably, patients who display these immunologic profiles are more likely to respond to subsequent biologic therapy.